Correlation and Path Coefficient Studies in Casuarina equisetifolia L. Johnson - Kumar, Ashok; Paramathama, M. (Indian Forester, 2005)
Correlation and path coefficient studies were carried out in 44 clones of Casuarina equisetifolia L. Johnson a,ssembled from Tamil Nadu, Andhra Pradesh, Orissa and Pondicherry. Genotypic correlations were higher then phenotypic correlations in all the cases. All the traits studied viz. Plant height, collar diameter, number of branches, survival percent, chlorophyll content and suitability index were strongly associated with volume index except needle length which showed low but significant genotypic correlation with volume index. All the traits expressed a positive and significant genotypic inter-correlation among themselves. Path coefficient analysis revealed that suitability index registered the highest direct effect followed by total chlorophyll content and number of branches. Maximum positive indirect effect on volume index was exerted by number of branches through suitability index.